Flexural study of Nano concrete for structural elements - A review - Uma Chandru; Kaarthik M; Karthikadevi S; Jayandiran Ramkumar (PREPARE@u® | IEI Conferences, 2021)
Materials science is consistently one of the active research topics in present scenario with ultimate motive is to enhance the strength and durability of any materials. In civil engineering nano concrete becomes popular globally in present time which has potential to produce concrete with more strength and durable and it also considered as a concrete for future generations. This article presents brief information about performance of nano concrete under flexural strength. The article covers deep insight of previously published quality literature along with future scope and conclusion.